2023
DOI: 10.3390/logistics7040097
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Methodology for Enhancing Reverse Logistics Flows and Networks in Industry 5.0

Al-Amin Abba Dabo,
Amin Hosseinian-Far

Abstract: Background: This paper explores the potential of Industry 5.0 in driving societal transition to a circular economy. We focus on the strategic role of reverse logistics in this context, underlining its significance in optimizing resource use, reducing waste, and enhancing sustainable production and consumption patterns. Adopting sustainable industrial practices is critical to addressing global environmental challenges. Industry 5.0 offers opportunities for achieving these goals, particularly through the enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In addition, the analysis of the latest sources [41][42][43][44][45][46][47][48][49] also showed that the greatest attention is paid to the circular economy and civilian logistics, as well as aspects of reverse logistics in it, while such a significant aspect as the interaction of circular and reverse logistics in the military sector is almost not examined. Therefore, this gap allows us to assume and inspire further discussion at the level of scientific research.…”
Section: Disposalmentioning
confidence: 99%
“…In addition, the analysis of the latest sources [41][42][43][44][45][46][47][48][49] also showed that the greatest attention is paid to the circular economy and civilian logistics, as well as aspects of reverse logistics in it, while such a significant aspect as the interaction of circular and reverse logistics in the military sector is almost not examined. Therefore, this gap allows us to assume and inspire further discussion at the level of scientific research.…”
Section: Disposalmentioning
confidence: 99%